An Analysis of Rhetorical Structures of Introduction Sections in International Conference Papers - Diyana Sulistyani; Januarius Mujiyanto; Suwandi Suwandi (Universitas Negeri Semarang, 2022)
Producing a well-organized and coherent text remains a significant problem in EFL context writing. Cognitive demands and low exposure to the language contribute to this issue. Numerous researches are available to tackle EFL learners’ texts by using various ways such as Theme/Rheme and thematic progression. Some studies attempt to uncover EFL texts’ coherence by using rhetorical moves and structure. This study attempted a novel method to reveal text coherence called Rhetorical Structure Theory (RST) by Mann and Thompson (1988). The data were the introduction sections of ten articles taken from the International Conference on Science, Education, and Technology (ISET) 2019, and they were analyzed by considering 23 relations in RST. The findings reveal that the Subject Matter relations category overpowers the number of Presentational relations. Elaboration ranks at the top with 72 data, followed by Background (19 times) and Purpose (18 times). However, there is no datum for Volitional Result, Otherwise, Interpretation, and Sequence relations. It suggests that the article writers preferred to provide information by giving a detailed explanation, a background of the case, and the study purposes. The results are expected to encourage future researchers to utilize various ways of tackling text coherence and to provide an alternative to analyzing text for educators.